2012
DOI: 10.1182/blood-2011-08-372003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional heterogeneity of human NK cells developing after umbilical cord blood transplantation: a role for human cytomegalovirus?

Abstract: Natural killer (NK) cells play a crucial role in early immunity after hematopoietic stem cell transplantation because they are the first lymphocyte subset recovering after the allograft. In this study, we analyzed the development of NK cells after intrabone umbilical cord blood (CB) transplantation in 18 adult patients with hematologic malignancies. Our data indicate that, also in this transplantation setting, NK cells are the first lymphoid population detectable in peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
190
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 232 publications
(203 citation statements)
references
References 50 publications
10
190
1
Order By: Relevance
“…The statistical significance (p value) is indicated. Graphic representations and statistical analyses were performed using the PASW Statistics version 20.0 software (formerly SPSS Statistics, IBM) (17) and GraphPad Prism 6 (GraphPad Software, La Jolla, CA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The statistical significance (p value) is indicated. Graphic representations and statistical analyses were performed using the PASW Statistics version 20.0 software (formerly SPSS Statistics, IBM) (17) and GraphPad Prism 6 (GraphPad Software, La Jolla, CA).…”
Section: Resultsmentioning
confidence: 99%
“…The medium used throughout the experiments was RPMI 1640 supplemented with 2 mM L-glutamine, 1% penicillin-streptomycin-neomycin mixture, and 10% heat-inactivated FCS (17).…”
Section: Isolation and Culture Of Nk Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study suggested that, in analogy to the MCMV model, interactions between the CD94-NKG2C receptor and ligands on HCMV-infected cells might drive the generation of a memory NK cell subset. Subsequent studies of patients who were infected by HCMV or in whom the virus was reactivated owing to immunosuppression after solid organ or haematop oietic stem cell transplantation confirmed that the CD94-NKG2C + NK cell population preferentially expands during acute HCMV infection, subsequently persist as memory cells and can constitute up to 70% of the total NK cell population in some individuals [34][35][36] . Moreover, after haematopoietic stem cell transplantation, CD94-NKG2C + NK cells from HCMV-seropositive donors demonstrated enhanced function in response to re-exposure to HCMV in HCMV-seropositive recipients whereas CD94-NKG2C + NK cells from HCMVseronegative donors did not, suggesting the existence of a memory response against HCMV infection 37 .…”
Section: Box 1 | Memory In Myeloid Cells In Mammalsmentioning
confidence: 98%